Reparations and Reconciliation: Legal Mechanisms for Addressing Historical Injustices Against Minorities in Indonesia (Indonesian Minority Justice Review, 2025)
This paper examines the legal mechanisms available for addressing historical injustices faced by minority groups in Indonesia, with a particular focus on reparations and reconciliation processes. Indonesia’s history is marked by numerous instances of state-sanctioned violence, discrimination, and land dispossession that disproportionately affected ethnic, religious, and indigenous minorities. The study reviews Indonesia’s legal framework for historical justice, including the 2004 Law on Human Rights Tribunals, and examines how these laws have been applied—or under-applied—to the historical injustices committed against various minority groups. The paper explores the concept of reparations as a means of acknowledging past wrongs and the legal pathways that might be employed to provide restitution, whether financial, symbolic, or in the form of land rights. Using case studies of indigenous land disputes, the 1965 anti-communist purge, and the treatment of religious minorities, the paper highlights the limitations of existing legal mechanisms and the gaps in Indonesia's national reconciliation efforts. The study concludes by advocating for a comprehensive reparations framework, including a truth and reconciliation commission, targeted legal reforms, and community-driven processes that can provide justice for Indonesia’s marginalized groups.